2019
DOI: 10.15537/smj.2019.10.24548
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric residents’ perceptions of the impact of the 24-hour on-call system on their well-being and education and patient safety

Abstract: Impact of the 24-hour on-call system on pediatric residents ... Alsohime

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…A study was conducted in Saudi Arabia supported the same nding in which the 24hour on-call system had a negative outcome on the residents' health, education, and safety of the patients. It suggested to investigate the impact of the duration of time residents spend in the hospital on their clinical performance, education, and quality of patient management [1]. Our study, showed that NF system had signi cant improvement in these three aspects.…”
Section: Discussion and Literature Reviewmentioning
confidence: 72%
See 1 more Smart Citation
“…A study was conducted in Saudi Arabia supported the same nding in which the 24hour on-call system had a negative outcome on the residents' health, education, and safety of the patients. It suggested to investigate the impact of the duration of time residents spend in the hospital on their clinical performance, education, and quality of patient management [1]. Our study, showed that NF system had signi cant improvement in these three aspects.…”
Section: Discussion and Literature Reviewmentioning
confidence: 72%
“…The Saudi Commission for Health Specialties introduced some guidelines regarding duty hour's regulations including the 24-hour on-call traditional shift system. The number of on-calls for pediatric residents in the rst two years of the training program should not exceed 7 on-calls every month while for residents in the third and fourth year of the program should not exceed 6 every month according to Pediatric Residency Training Program Manual [1].…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted in Saudi Arabia supported the same nding in which the 24hour on-call system had a negative outcome on the residents' health, education, and safety of the patients. It suggested to investigate the impact of the duration of time residents spend in the hospital on their clinical performance, education, and quality of patient management [1]. Our study, showed that NF system was perceived with signi cant improvement in these three aspects.…”
Section: Perceptions Of the Impact Of The Night Float Systemmentioning
confidence: 75%
“…Furthermore, an increase in incidence in burnout and suicide attempts among physicians have been reported. As a result, several countries have established a new system of work coverage called the Night Float (NF) shifts system and abandon the traditional 24-hours on-call system [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation